Pengembangan Media Pembelajaran Aplikasi Canva pada Pembelajaran Tematik Tema Benda, Hewan dan Tanaman di Sekitarku Kelas I SD Muhammadiyah Sei Rampah - Lubis, Ayu Puspita Sari; Silalahi, Beta Rapita (Medan Resource Center, 2023)
The purpose of this research is to develop a Canva application-based learning environment for thematic learning on the subject of objects, animals, and plants around me in Class I. The research adopts the Research and Development model, focusing on product development. The study involved teacher interviews, with 75% of the teachers expressing the importance of using the Canva application in the learning process. The Canva application positively influenced thematic learning outcomes in Class I, as evidenced by the dominant respondents giving a validity level of